Asian Christianity and Civil Society Organizations in the Context of Conflict in Manipur - Alifina, N. (University of jaffna, 2024)
Asian Christianity without touching the social realities cannot produce a relevant theology. In the context of conflict and violence, the role played by the Asian Christianity especially the “Indian Christian” in the state of Manipur needs to be re-examined. In a state like Manipur, conflict has always been a part of life and it is inevitable due to the presence of multi-ethnicities, multi-religions, and different cultural practices. The current conflict in Manipur has also made the Meitei Christian vulnerable and helpless. The Meitei churches are unable to “speak” hence a response of “silence” is upheld. In a time of political disharmony and animosities in Manipur, it is the people’s movement that has come to express their civil roles in the state. They represent the interest of the citizens. The Civil Society Organizations (CSO’s) play a crucial intermediary role between the state government and the citizens. Instead of trusting on the state government, the people of the state now rely on the CSO’s. It is discernible that the CSO’s struggles to bring out a solution to this ongoing crisis. Despite their limitation, one cannot deny their roles in containing the situation while at the same time aggravating it. The CSO’s must identify the problem, not on “who” but “what” is the problem and “how” do we tackle against the real crux of the problem. Civil Society Organizations should be the space where the diverse needs of the citizens are addressed. Helio Gallardo writes that “Civil Society” is an ecumenical space in which everyone appreciates and values other cultures and religions as manifestations of the richness of the one God of life.
Keywords: Violence in manipur; Role of civil society organizations; Ecumenical space